Observations on Adıyaman Gölbaşı after the Earthquake and Architecture - Rojat Aksoy Işık (Doğal Afetler ve Çevre Dergisi)
Earthquakes, which are considered to be one of the natural disasters/hazards that cannot be prevented, are movements that shake the environments where vibrations arising from fractures in the earth's crust spread in the form of waves. Earthquakes are an inevitable reality in Turkey, which is located in the earthquake zone. Many earthquakes have occurred in Turkey to date and will continue to occur. Among the recent earthquakes, the earthquakes with a magnitude of 7.7 (centered in Pazarcık) and 7.6 (centered in Elbistan) in Kahramanmaraş on February 6, 2023 are among the earthquakes. The epicenter and 11 provinces around it (Kahramanmaraş, Hatay, Adıyaman, Osmaniye, Gaziantep, Şanlıurfa, Malatya, Diyarbakır, Adana, Kilis and Elazığ) were greatly affected by this Pazarcık-centered earthquake. This high-intensity earthquake greatly affected many settlements and structures here. The Gölbaşı district of Adıyaman, one of the settlements most affected by these earthquakes, was included in the scope of the study. On April 26, 2023 (79 days after the earthquake), MAU Engineering-Architecture Faculty Architecture Department professors and students went to Gölbaşı and made on-site observations and investigations. The places where observation and examination were carried out are Fatih and Yeni neighborhoods of Gölbaşı Center. The main purpose of the research is to understand the causes of these damages and to examine the earthquake-architecture relationship. Observations have shown that many buildings were damaged due to ground liquefaction, and that structural damage was also significant. Literature review reveals that there are not enough studies on the relationship between architecture and earthquakes. This situation emphasizes that post-earthquake building design and construction processes need to be reconsidered. The results of this study may contribute to the development of architectural approaches to build more resistant structures against future earthquakes. As a result, such studies provide important data for post-earthquake damage assessment as well as for improving structural design. In countries such as Türkiye, which are located in earthquake zones, the effort of architecture and engineering disciplines to work together to create a safer living space is of great importance.